Factors related to sentinel node identification in cervical cancer - Phanida Jarruwale; Kuan-Gen Huang; Doris R. Benavides; Chyi-Long Lee (Gynecology and Minimally Invasive Therapy, 2012)
Cervical cancer remains a common malignancy in women. Lymph node is one of the significant important prognostic factors. Until now, there is no reliable investigative study that can evaluate nodal status the same as the International Federation of Gynecology and Obstetrics (FIGO) clinical staging system. Radical hysterectomy and pelvic lymphadenectomy is still one option in the standard treatment of patients with early-stage cervical cancer that can reveal metastatic lymph node but which can also produce treatment-related morbidities and complications. Sentinel lymph node identification has become a valuable technique for nodal status assessment. If lymph node metastasis was identified early, then unnecessary invasive surgical operations and complications may be avoided.